PLURALISME PERSPEKTIF ISLAM METODE TAFSIR MAUDHU’I - Nazwa Laela Imtihadah; Nilam Cahya Safitri; Nur Muhamad Iskandar; Rizki Rahmat Fadilah (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
Religious pluralism is often seen as providing solutions that promise noble hopes and human values, even though it is not yet known whether this concept is good or not to be used as a guide, especially for Muslims. This study aims to examine the concept of pluralism in the Qur’an, so that it is known whether this concept is good or not to be used as a guide, especially for Muslims. The research methodology taken is the library research method. This Tafseer study requires data collection because search relies on existing literature. His type of research is qualitative research, namely efforts made to expand the discussion with accurate data. The conclusion of this study shows that, religious pluralism is an understanding that explains that all religions are the same, this concept is not the same as understanding tolerance. The view of the Qur’an towards pluralism is of course strongly rejected. We are prohibited from mixing, in this context religious teachings.